Клинико-иммунологические фенотипы РАС – новая возможность персональной терапии - Khudyakova, M. I.; Cherevko, N. A.; Klimov, V. V.; Novikov, P. S.; Nikitina, A. A.; Denisov, A. A. (Патогенез, 2022)
Тезисы конференции